Karakteristik Kayu Cepat Tumbuh Terimpregnasi Monoetilen Glikol dan Nanopartikel SiO 2 terhadap Serangan Jamur Pelapuk Kayu - Rahayu, Istie; Saputri, Egydia; Priadi, Trisna; Wahyuningtyas, Irma; Prihatini, Esti; Ismail, Rohmat (Universitas Gadjah Mada, 2024)
Jabon (Anthocephalus cadamba) and Sengon (Falcataria moluccana) were fast-growing wood species widely planted in the community forest. Both kinds of wood have low durability even though they can potentially be used in the carpentry material industry. Therefore, this research aimed to analyze the vacuum-pressure impregnation effect using monoethylene glycol (C2H6O2) or MEG and silica dioxide (SiO2) nanoparticles on wood resistance to fungal decay. The results showed that impregnation treatment with MEG and SiO2 nanoparticles significantly improved the durability of Jabon and Sengon against fungal attacks. Furthermore, MEGSiO2 with 24-hour polymerization had a better impact on durability compared to both the control and MEGSiO2 with 12-hour polymerization. The 24-hour polymerization using 1% SiO2 nanoparticles resulted in the lowest weight loss for Jabon (5.86% ) and Sengon (5.21%). In addition, the variation of SiO2 nanoparticle concentration did not significantly affect the weight loss and durability of Jabon and Sengon against fungal decay.